What is the socio-linguistic context for teaching English writing to senior high school students in Fiji? : a thesis completed in fulfilment of the requirements for the degree of Master of Philosophy (Humanities and Social Sciences) in Second Language Teaching, Massey University, Palmerston North, New Zealand - Nicholls, Lynn (Massey University, 2014)
This study explores teaching practices for expository writing in a developing world context. A qualitative approach draws on a grounded theory model with three different high school case studies in Suva, Fiji. The participants were teachers and students from Form 6 English classes. The linguistic landscape is diverse, with the two majority ethnicities comprising of indigenous Fijian and Fijian both learning different vernacular languages as mediums of instruction for the first three years of school. Standard Fijian and Standard Hindi taught in schools are not always the languages these students speak at home. While English is the medium of instruction taught in schools from Class 4, there is no official language of instruction policy. Students who have English as their second language face challenges in achieving the academic genre of writing. A pass criterion for English proficiency comes with high stakes for success in tertiary studies, with writing for examinations being the only method of assessment. The study found that teachers lacked appropriate resources for teaching this genre of writing, and therefore resorted to teaching more simple formal writing options. Teacher training and professional development in the areas of second language teaching and unit writing appear inadequate in supporting the teaching and learning writing process, and as a result students may not be adequately prepared for their aspirations of going to university.
Keywords: English language; Rhetoric; Writing; Composition; Study and teaching; Fijian language; Hindi language; Second language teaching; Social aspects; Suva; Fiji; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::Subject didactics